Treatment Challenges in a Tourette Syndrome Patient with Self-Injurious Behaviour: Case Report and Literature Review - Asadauskaitė, G.; Jasionytė, G.; Karnickas, M. (Neurologijos seminarai, 2023)
Introduction. Tourette syndrome is known as a combined vocal and multiple motor tic disorder. It is a chronic complex neuropsychiatric disorder characterised by the onset of symptoms in early childhood and the presence of multiple motor tics and one or more vocal tics. In most cases, the symptoms resolve or become less severe in early adulthood. Nevertheless, there are some cases where the syndrome does not follow its typical clinical course.Case report. We present a 28-year-old patient with Tourette syndrome. The patient was hospitalized for complex motor and vocal tics, as well as tics resulting in self-harm. First tics began at the age of twelve and gradually intensified. The patient was diagnosed with Tourette syndrome at thirteen and has been taking Haloperidol 5 mg 3 times a day and Trihexyphenidyl 2 mg 3 times a day for the past 15 years. His condition worsened 6 months ago with increased tics, self-harm, insomnia, social withdrawal, and weight loss. In the hospital, Haloperidol was gradually replaced with 20 mg of Aripiprazole daily. The patient underwent twenty-six transcranial magnetic stimulation procedures. During hospitalization, insomnia was resolved, whereas motor tics and self-harm decreased.Discussion. The pathogenesis of Tourette syndrome emphasizes the dysfunction of neuronal networks in the basal ganglia. It leads to impaired inhibition in the sensorimotor cortex of the brain, which results in motor and vocal tics. Their characteristics are individual to each patient. The course of illness and the severity of symptoms are influenced by various stressors, intense emotional experiences, and environmental factors. Tourette syndrome is commonly treated with psychotherapy, pharmacological treatment, or a combination of these methods. The case we present shows that the conventional treatment methods are not always effective, and that the clinical course of Tourette syndrome may deviate from the usual expressions of the syndrome.
Keywords: Tourette syndrome; self-injurious behaviour; aripiprazole; transcranial magnetic stimulation